'A bad child has his own day': Gwama Boys and post-conflict peacebuilding dilemma in oil-bearing communities of Ondo state, Nigeria. Issue 2 (3rd April 2022) - Olaniyan, Azeez
ABSTRACT: Gwama Boys is one of the ethnic militias in the oil-bearing communities of Nigeria. But while others militias in the area have been subjected to research, little is known of Gwama Boys. Yet its emergence and continued existence constitute a major dilemma in the post-conflict peace-building process of the area. Specifically, Gwama Boys emerged among the Ilaje ethnic group in their war against Ijaw group in the late 1990s over issues concerning land and oil. Long after the war, the group has remained intact and constituting security challenges onto the communities. On several occasions, they have been fingered in acts of kidnapping, robbery and oil pipeline vandalism. Yet, in spite of these atrocities, the people still prefer to have them around. The study made use of both primary a nd secondary data. The main method of data collection was unstructured interview conducted with a number of critical respondents. Theory territorial imperative was adapted for the study and findings show that Gwama Boys were created as a countervailing ethnic militia to prosecute a war. Long after the war, the group has been kept as a standby force against anticipated attack by an enemy next door.